The Clinical Characteristics and Pathological Patterns of Postinfectious Glomerulonephritis in HIV-Infected Patients - Murakami, Christine A. (Public Library of Science, 2014)
BACKGROUND: Postinfectious glomerulonephritis (PIGN), a form of immune complex GN, is not well-defined in HIV-infected patients. This study characterizes PIGN in this patients’ population and determine the impact of histopathological patterns on renal outcome and mortality. METHODS: HIV-infected patients with PIGN from September 1998 to July 2013 were identified. Archived slides were reviewed by a blinded renal pathologist, classified into acute, persistent and healed PIGN. Groups were compared using Wilcoxon rank-sum and Fisher’s exact test. Survival analyses were performed to determine association of histopathological pattern with renal outcome and mortality. RESULTS: Seventy-two HIV-infected predominantly African American males were identified with PIGN. Median (interquartile range) age and creatinine at the time of renal biopsy was 48 years (41, 53) and 2.5 mg/dl (1.5, 4.9) respectively. Only 2 (3%) had acute PIGN, 42 (58%) had persistent PIGN and 28 (39%) had healed PIGN. Three patients (4%) had IgA-dominant PIGN. Only 46% of the patients had confirmed positive cultures with Staphylococcus the most common infectious agent. During a median follow up of 17 months, the pathological pattern had no impact on renal outcome (P = 0.95). Overall mortality was high occurring in 14 patients (19%); patients with healed PIGN had significantly increased mortality (P = 0.05). CONCLUSION: In HIV-infected patients, Staphylococcus is the most common cause of PIGN. Renal outcome was not influenced by the histopathological pattern but those with healed PIGN had greater mortality which was potentially due to a confounder not accounted for in the study.